Problem solvers! IN Features. - Aguilera, Ray.; Berenstain, Adam.; Baldwin, Roberto; Ochs, Susie; Simon, Michael; Vargus, Nic.
A list of 25 Mac, iOS, and web apps that solve 25 of life?s peskiest problems.
Keywords: iPhone (Smartphone).; iPad (Computer).; Mac OS; Mobile apps; iOS apps